Use of allergen immunotherapy for treatment of allergic conjunctivitis. Issue 6 (December 2020) - Norris, Matthew R.; Khaimov, Michelle; Bielory, Leonard
Abstract : Purpose of review: The purpose of this article is to provide an overview of the literature pertaining to the use of allergen immunotherapy for treatment of allergic conjunctivitis with an emphasis on recent developments. Recent findings: Both subcutaneous (SCIT) and sublingual (SLIT) immunotherapy continue to show efficacy in treating allergic conjunctival disease, subcutaneous more than sublingual. Adverse effects of sublingual therapy continue to be reported since the FDA's approval of SLIT tablets in 2014. Initial SLIT studies reported high rates of adherence, while real use reports identify rates of nonadherence/discontinuation ranging between 50 and 80%. Studies in polyallergic patients evaluating the efficacy of SLIT combination therapy report encouraging results. Summary: Both SCIT and SLIT offers improvement in allergic conjunctival symptom scores and decrease medication utilization. Although SCIT has a higher likelihood of systemic reaction, SLIT has a very high rate of mild-to-moderate adverse events – especially in the first month. Cost–benefit analyses tend to favor SCIT (greater efficacy and less impacted by discontinuation rates).